Ba, Co modified activated clay and their adsorption performance characterization. Issue 1 (May 2021) - Yang, Jie; Wang, Yajun; Tian, Changan; Lai, Shikang; Liu, Yang; Si, Xiaoqiang; Zhang, Qing
Abstract: A series of modified activated clay composite materials were prepared by solvothermal method. The modified samples were tested and characterized by a series of instrument methods. The modified activated clay materials with good adsorption effect, simple process and low cost were synthesized by doping different metal ions. The adsorption properties of the modified activated clay materials were investigated. The results show that the (Ba, Co)-activated clay modified samples can be used as adsorbents to remove Congo red organic dye wastewater, and the activity is greatly improved compared with the activated clay, the adsorption capacity is greatly enhanced. The particle size is small, and it has good thermal stability. When the initial Congo red concentration is 100 mg/L and the adsorption time is 140 minutes, the maximum adsorption capacity of Ba-activated clay is 371 mg/g, and that of Co-activated clay is 338 mg/g.